Fatigue assessment of load-carrying welded cruciform joints - S.V. Petinov (Инженерно-строительный журнал, 2013)
T-form and cruciform joints in which the stress flow is transferred via weld material are widely applied in welded structures. A special type of these joints is presented by fillet-welded joints with incomplete penetration used by economical and manufacturing reasons. At a certain width of the cavity it becomes an active notch which in current design rules is regarded as an initial crack. In that way, fatigue life of the joint is characterized by the crack extensions towards the outer surface of weld bead. Fatigue assessment of these joints requires reliable data on the stress intensity factors values along the crack path. The results of systematic FEA-based calculations of stress intensity factors and respective S-N curves for the considered welded joints are presented. Main results obtained during this investigation can be used in solution of engineering tasks in reference to the fatigue assessment of welded cruciform joints with incomplete penetration.